Evaluating trustworthiness of artificial intelligence (AI) applications in education - Mohammed Ebnu Saifudin, Nurul Afiqah; Anwar, Norizan; Hashim, Husain; Harisanty, Dessy (Faculty of Information Management, 2025)
Artificial intelligence (AI) is a high-paced evolving technology that is now being implemented on internet platforms. This massive advancement has the capability to drastically change our daily lives as humans, especially in the educational sector. AI is user-friendly and can assist in students' research work. AI-powered robots are being used to enhance the efficiency and convenience of daily tasks. This research focused on the factors of trustworthiness in AI applications that need to be further investigated.